Lecturers’ perceptions of a semester-wide interdisciplinary PBL in a master’s degree program in industrial engineering and management - Moreira, Francisco (2018)
The present study, conducted at the end of a PBL edition at the University of Minho, reports on the results of a questionnaire issued to the lecturers of the Project Supporting Courses of a semester-wide interdisciplinary PBL approach. The questionnaire was intended to gather the perceptions on a number of relevant aspects, such as on the validity and acceptance of the PBL methodology, dynamics of team-based learning and its impact on development of transversal competences, the assessment methodology in place, the learning process and development of technical competences, the impact of choosing a project theme and leave it open, and, additionally, to acquire other relevant perspectives on the running of the project. This study aims to close the loop regarding a continuous and ongoing improvement process of the PBL approach. The results show that the lecturers acknowledge PBL as a valid learning methodology on the IEM field; that the chosen theme was contemporary and stimulating; provided an excelling experience on the development of communication competences, among others. They also point out the excessive size of the teams and call the attention to the specialization problem inside the teams. The assessment mechanism in place seems to require further attention.